Bakti Sosial Donor Darah Serta Pemeriksaan Kesehatan Bersama PMI dan IDI Padangsidimpuan di Kantor Walikota Padangsidimpuan - Nasution, Dina Rahmi Solihad; Nasution, Izmi Fadhilah; Hasibuan, Elmi Sariani; Handayani, Fitri Rahma (Universitas Aufa Royhan Di Kota Padangsidipuan, 2023)
Blood donation is an activity to take blood from voluntarily which will be stored in blood bank for blood transfusion purposes. Blood transfusion is an activity of transferring blood between donors to recipients with certain terms and conditions. It is necessary to treat the condition of lack of blood in one individual. The purpose of this community service was to add insight into the benefits of blood transfusions both for one's own person and for others in need. This activity was held on October 29, 2023 at the Padangsidimpuan Mayor's Office. The series of this activity were fun walk, health checks and blood donations. This community service used a participatory model. The results of this activity were obtained 70 voluntary blood donor participants consisting of adolescents to adults and then obtained 70 bags of blood products. Thus, this community service is beneficial as a medium for independent health promotion to increase public interest in donating blood